Menguji Sikap Implisit Dengan Implicit Association Test - Hafiyah, Nurlyta; Puri, Anisa; Shadewi, Rizkiana (UI Scholars Hub, 2011)
The present study was aimed to develop implicit association test (IAT) as a measure of implicit attitude and to test whether IAT had good validity and reliability to measure implicit attitude between Moslems and Christians in Indonesia. Both Moslems and Christians were participated in this study. The results showed that IAT is valid and reliable to measure implicit attitude related to religion. Furthermore, IAT was able to reveal more attitudinal discrimination between Moslem and Christian categories than it would be revealed by the explicit measures of the same religion-related attitude. IAT was also able to reveal opposed evaluations even for participants who deny, on self-report measures, any prejudice toward their out-group. Whether IAT effects indicated prejudice is discussed.